Regional imbalance in nursing workforce: a system dynamics approach focusing on wages and job attractiveness - Sohyun Lee; Eun Kyoung Yun (Journal of Korean Academy of Nursing, 2026)
Purpose: This study used a system dynamics approach to analyze the feedback structure underlying regional imbalance in the nursing workforce in Korea and to evaluate the projected effects of policy interventions through simulation.Methods: A system dynamics model was developed using literature and public statistics from the Graduate Occupation Mobility Survey and the Korean Statistical Information Service for 2009–2024. Model validity was assessed through sensitivity analysis and comparison with historical data from 2018–2022. Policy simulations covering 2020–2035 were conducted to compare interventions targeting wages and working conditions in Seoul and Jeonnam.Results: The analysis identified 16 feedback loops, comprising 13 reinforcing loops and three balancing loops, that formed a “success to the successful” structure dominated by a reinforcing cycle of high turnover. In the baseline simulation, the regional gap widened through 2035. Single-factor scenarios involving wage increases or improvements in working conditions had limited effects, whereas high-intensity combined scenarios showed a synergistic effect that could reverse the projected imbalance.Conclusion: Regional imbalance in the nursing workforce appears to be a structural problem that is unlikely to be resolved through single-factor policies. Sustained, high-intensity strategies that combine wage improvement with nonfinancial improvements in working conditions are likely needed to disrupt the reinforcing cycle and reduce the nursing workforce imbalance.